Directions For Improving Service Efficiency In Banks Through Digital Technologies - To‘rayev Azamat Shuxratovich (Genius Publishing Group, 2025)
The purpose of the article is to increase the efficiency of service provision in banks through digital technologies. Accordingly, this article considers the need to introduce an innovation mechanism in commercial banking. In addition, proposals are made to introduce an innovation mechanism in commercial banking through digital technologies.
Keywords: Innovation; efficiency; commercial banks